Gamiting Ekspresyon Ng Wikang Adbertaysment at Pagtangkilik Sa Produkto - Tayong, Necita (JPAIR Multidisciplinary Research, 2017)
This study aimed to measure and appreciate the use of the expression of language and product support. A descriptive approach was utilized. There are two-hundred fifty (250) students from Universities de Zamboanga, Western Mindanao State University, Southern City Colleges, and Zamboanga State College of Marine Science and Technology. A questionnaire survey was used as a data gathering instrument. Data collection tests used frequency counts, percentages and meanings as statistical equipment. From the computation done, the students found five more products: Safeguard bath soap, Colgate toothpaste, Maggie noodles, Biogesic tablets and Clear shampoo. The expressions lead the most effective and clear the following: "skin protection, scent protection, excellence in skin protection, strengthens hair to reduce breakage and hair fall defense. It is noteworthy in the expressions of the language used in the advertricted products of the product according to the credibility of the product endorsed and delivered the 'scent protection' effect is on top,  second is "skin protection", third is "Excellence in skin protection", fourth is the product "strengthens hair to reduce breakage" and the fifth is "hair fall defense."
Keywords: Advertisement; expression; information; product; descriptive design; Philippines